Student satisfaction and online teaching. Issue 7 (3rd October 2018) - Guest, Ross; Rohde, Nicholas; Selvanathan, Saroja; Soesmanto, Tommy
Abstract: This paper presents an analysis of the response of student satisfaction scores to online delivery for courses at a large Australian university. Taking data from 2653 courses delivered since 2011 we employ a difference-in-differences estimator approach to evaluate the impact of a transition from face-to-face learning to online learning of courses on student satisfaction. We estimate that, on a five-point scale, conversion to online learning lowers course satisfaction by about 0.2 points and instructor satisfaction by about 0.15 points. These correspond to shifts relative to the underlying distributions of about 25–30% of a standard deviation. Some implications of the (slight) relative unpopularity of online learning are discussed.